Model pengembangan usaha tani sagu di Kabupaten Luwu Utara, Provinsi Sulawesi Selatan: Sago farming development model in North Luwu Regency, South Sulawesi Province - Nuryanti, Dewi Marwati; Haruna, Naima; Sumantri; Hidayat, Muhammad Aqhsal; Lisma; Adriani, Yiyis (Analisis Kebijakan Pertanian, 2025)
North Luwu Regency, South Sulawesi Province has great potential as a sago-producing area; however, its management still faces challenges, including low productivity, limited adoption of technology, and limited market access. This study aims to develop a sago farming business model in North Luwu Regency using analytical methods the Participatory Prospective Analysis (PPA) and Strengths, Weaknesses, Opportunities, and Threats (SWOT) analyses. This study involved 120 farmer respondents, 24 sago processors, and seven experts. This study came up with recommendation of a sago farming business development model Y = f (S1-3; W1-2; O1-7; T1-4): optimizing sago farming business development by utilizing internal strengths (easy to cultivate, high productivity, and multipurpose plants) and external opportunities (product diversification, increasing market demand, industrial raw materials, increasing demand for sago food, technological innovation, land expansion and support from financial institutions). The priority strategies are located in the SO quadrant (aggressive strategy), with policy implementation focused on the extensification of idle land using modern technology, product diversification based on international markets, and strengthening access to financing. These policy recommendations provide strategic solutions to increase productivity, local economic sustainability, and food security.